A U-shaped relationship between the atherogenic index of plasma and repeated target vessel revascularization in patients undergoing percutaneous coronary intervention: a retrospective study - Huang, Xingjie; Wen, Song; Huang, Zehan; Qin, Guishi; Zhou, Hanli; Xia, Zhonghua (Frontiers in Endocrinology, 2024)
Background: Atherogenic index of plasma (AIP) has been recognized as a novel and practical marker for the assessment of cardiometabolic risk, but the relevance of AIP as a prognostic biomarker in coronary artery disease (CAD) remains debated. This study investigated the association between AIP and major adverse cardiac and cerebrovascular events (MACCEs) in CAD patients receiving percutaneous coronary intervention (PCI) with drug-eluting stents (DES).Methods: A total of 2,250 patients undergoing PCI with DES were included in this retrospective cohort study. The primary endpoint was MACCEs, encompassing acute myocardial infarction, repeat target vessel revascularization (TVR), stroke, and all-cause mortality. Logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Restricted cubic splines were applied to explore the dose-response associations. And subgroup analysis was conducted to evaluate potential relationship between AIP and MACCEs across different subgroups.Results: During a medium follow-up of 29.8 (25.6-34.0) months, 106 (4.7%) patients experienced TVR. After adjusting for confounders, AIP (per 1 SD increase) was positively associated with TVR (odds ratio [OR] = 1.26, 3 95% confidence interval [CI] = 1.01-1.58, P = 0.042). In females, there was a significant association (OR = 2.33, 95% CI = 1.40-3.98, P = 0.002), but no significant association was observed in males. There was an interaction between AIP and gender (P = 0.017). Restricted cubic spline analysis depicted a U-shaped relationship between AIP and TVR (Pnonlinear = 0.016), with an elevated risk evident from an AIP of 0.20.Conclusion：AIP showed a U-shaped relationship with TVR in PCI patients with DES, particularly pronounced among females. We suggested that the AIP should be used as a plasma marker of key interest for preventing TVR after DES implantation in patients with CAD.